Evaluación de diferentes genotipos de uvilla (Physalis peruviana L.) y dos paquetes tecnológicos en el cantón Loja - Armijos Chuncho, Silvia Patricia (2020)
The golden berry (Physalis peruviana L.) commonly known as uvilla is a herbaceous species belonging to the Solanaceae family, currently the uvilla is considered one of the most exotic fruit trees in exports in several Andean countries and therefore its production is in constant boom, it adapts very well to Andean areas between 1500 and 3000 m. s. n. m. In Ecuador it is commonly known as uvilla, The economic importance of this species lies in it sugary fruit, presents great potential, good perspectives and interest in international markets, can establish like a stable crop with the end to improve the internal economy of a lot of countries, but, still exists scarce information about systems of production, productive chain and handle phytosanitary. The present study is carried out with the purpose to determine the response of four genotypes of goldenberry (Physalis peruviana L.) and two technological packages under the climatic conditions of the Loja canton. The study was developed to open field during October 2019 to March 2020, under a completely randomized design of plots divided, where the technological package represents the main plot and the genotypes (wild lojano, cultivate lojano and quiteño Tankay 1 and 2) the subplots; 8 treatments were established with four repetitions. The data collection for vegetative variables of plant height (AP), stem cross-sectional area (ASTT), number and length of shoot and metameric (NB; NM; LB and LM) were carried out every 21 days after the transplantation, while the variables to know the production and quality of fruit such as number of fruits per plant (NFP), the weight of the fruit with and without cap (PFCC; PFSC), estimated yield (RE), percentage of fruits formed (FC), titratable acidity (AT), total soluble solids (SST), percentage of cracked fruits (FR) and classification of fruit size (CT) were performed at the end of the experiment. Also, reproductive phenology was determined based on the thermal time (IT). Inside the vegetative, productive and quality parameters stands out the treatment P1G2, the interaction between the technological package 1 and the genotype cultivate lojano, with an upper vegetative development of 166,2 cm, 457 NFP, a RE of 3,12 kg/plants, a PFCC of 7,2 g; 6% of FR, and 85% of FC. Also The lojanos genotypes (wild lojano and cultivate lojano) showed a lower thermal request until the physiological maturity with 1560, 0 and 1571, 1 degree days (°Cd) respectively, whereas, the quiteños genotypes requires a greater thermal accumulation of 1606, 7 and 1616, 04 degree days (°Cd) Keywords: agricultural production system, yield, thermal time, phenology.